SEGMENTASI PASAR, SELEKSI PASAR SASARAN, DAN POSITIONING PADA INDUSTRI JASA: SUATU TINJAUAN LITERATUR SISTEMATIS - Sinarwaty; Vina Mustika Sidiq; Hasir Hasir (SINERGI : Jurnal Riset Ilmiah, 2026)
This research synthesizes cutting-edge research on market segmentation, target market selection, and positioning in the service industry. The review is designed as a structured qualitative synthesis of Scopus indexed journal article documents published in the period 2020-2026. A total of 1,282 article documents were identified in the early stages. After filtering titles, abstracts, keywords, language, and conceptual suitability, as many as 80 article documents were retained for qualitative synthesis. The findings show that segmentation is the most dominant research stream, while studies that explicitly discuss target market selection are still relatively limited. The literature is heavily concentrated on tourism and hospitality, but meaningful expansion is beginning to emerge in the healthcare, banking, fintech, higher education, retail, and platform-based services sectors. Across the studies examined, segmentation has shifted from static demographic logic to a motivation, value, behavior, and analytics-based approach. Target market selection is increasingly understood as a multi-criteria decision-making issue that must balance market attractiveness, sustainability, and channel suitability. Positioning research emphasizes brand congruence, digital signaling, user-generated content, and differentiated value communication in service encounters. The main contribution of this review is to consolidate fragmented evidence into an integrated STP lens, affirm the dominance of the current tourism context, and propose a future research agenda centered on dynamic segmentation, cross-sector validation, and strengthening the linkages between STP decisions and service performance outputs.